Species diversity and spatial distribution of bats in Butuan City, Philippines - PAUL JOHN B. PASTOR; CHRISTIAN GUILLEMORE O. SUSI; JEDIDIAH JARA QUIDET; JUVY IMEE A. LADESMA; LEONARDO A. ESTAÑO (Society for Indonesian Biodiversity, 2024)
Abstract. Pastor PJB, Susi CGO, Quidet JJ, Ladesma JIA, Estaño LA. 2024. Species diversity and spatial distribution of bats in Butuan City, Philippines. Biodiversitas 25: 2791-2799. Southeast Asia's mammalian biodiversity is exceptional in the Philippines, especially on Mindanao Island, where 53 bat species have been documented. While prior studies in the Caraga region identified vulnerable and endemic bat species, research on diversity and conservation in Butuan City remains limited. Bat biodiversity is essential in the country, and understanding Butuan City's bat populations is critical for conservation. This study recorded a total of 2,583 bats belonging to the family Pteropodidae with species Ptenochirus jagori Peters 1861, Ptenochirus minor Yoshiyuki 1979, Macroglossus minimus E.Geoffroy 1810, Cynopterus brachyotis Müller 1838, Rousettous amplexicaudatus E.Geoffroy 1810, as well as Scotophilus kuhlii Leach 1821 belonging to the family Vespertillionidae. Across six sampling sites, moderate species richness of Pteropodidae bats was observed (Shannon-Weiner Diversity Index, H' 1.13-1.47). However, analyses of evenness and dominance revealed variations in community structure. Barangay De Oro displayed the most balanced abundance, while other sites likely harbored a dominant species, potentially C. brachyotis or P. jagori. Bray-Curtis Similarity results corroborated these findings, grouping sites based on shared assemblages. Moreover, the significance of Butuan City for bat conservation is emphasized by the capture of a substantial proportion of a Philippine endemic (38.37%, P. jagori) and a Mindanao endemic (3.99%, P. minor). Distribution patterns across the sampled barangays suggested habitat specialization, with some species exhibiting preferences for specific features. Notably, S. kuhlii was captured exclusively in Ampayon. These findings highlight the need for multifaceted conservation strategies. Protecting core habitat areas within Bilay, Maguinda, and Sumile of Butuan, particularly for endemic species, is crucial.